2007
DOI: 10.1007/s00360-007-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-dependent changes in Na+/K+-ATPase content of mitochondria-rich cells contribute to differences in thermal tolerance of Mozambique tilapia

Abstract: The Mozambique tilapia (Oreochromis mossambicus) is prone to osmoregulatory disturbances when faced with fluctuating ambient temperatures. To investigate the underlying causes of this phenomenon, freshwater (FW)- and seawater (SW)-acclimated tilapia were transferred to 15, 25, or 35 degrees C for 2 weeks, and along with typically used indicators of osmoregulatory status [plasma osmolality and branchial and intestinal specific Na(+), K(+)-ATPase (NKA) activity], we used tissue microarrays (TMA) and laser-scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…At the same time, this antibody enabled us to quantify NKA abundance in individual MRC and to determine MRC size. While NKA antibodies have previously been used as a MRC marker (Lima and Kültz 2004;Sardella et al 2008) and MRC size has often been measured after live DAPSMI/DASPEI staining (Foskett et al 1981;Kültz et al 1992;Van Der Heijden et al 1997), the Wxation of whole cells on PLL-coated coverslips allowed us to combine these two approaches and utilize NKA antibodies for determination of MRC size in Wxed, dissociated cell populations. This method is advantageous over live cell stains such as DASPMI when co-labeling with dyes that require Wxed cells is desired (for instance TUNEL labeling) and also to measure NKA abundance per MRC.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this antibody enabled us to quantify NKA abundance in individual MRC and to determine MRC size. While NKA antibodies have previously been used as a MRC marker (Lima and Kültz 2004;Sardella et al 2008) and MRC size has often been measured after live DAPSMI/DASPEI staining (Foskett et al 1981;Kültz et al 1992;Van Der Heijden et al 1997), the Wxation of whole cells on PLL-coated coverslips allowed us to combine these two approaches and utilize NKA antibodies for determination of MRC size in Wxed, dissociated cell populations. This method is advantageous over live cell stains such as DASPMI when co-labeling with dyes that require Wxed cells is desired (for instance TUNEL labeling) and also to measure NKA abundance per MRC.…”
Section: Discussionmentioning
confidence: 99%
“…Values are means± in SW, the yolk sac membrane, rich in ionocytes and without the shunt formed by lamellae or edge damage, develops a V t of +50±1.7 mV (Guggino, 1980), so this value may be close to the upper limit that these salt-secreting systems can develop. In extremely high salinities of 95‰, Tilapia have elevated plasma Na + to 260 mmol l −1 (Sardella et al, 2008); the calculated E Na of +44.3 mV suggests that fish are forced to adjust their plasma Na + upward, so that the maximal V t can still produce Na + secretion via the paracellular pathway. In contrast, we found that the buccal epithelium, which has few ionocytes, develops much lower V t and I sc , which confirms previous findings (Karnaky, 1980), but we predict that buccal epithelium would not contribute to Na + secretion in SW or 2SW.…”
Section: Functional Interpretationmentioning
confidence: 99%
“…Because the previous studies have demonstrated that the specific NKA activity which was measured at the exposed temperature of fish would correlate with the level of in vivo activity (Metz et al 2003;Sardella et al, 2008a), therefore, the reaction was run at the exposure temperatures in this study. The concentration of inorganic phosphate was measured according to Doulgerakia et al (2002).…”
Section: Dot Blot Analysismentioning
confidence: 99%
“…Environmental temperature significantly influences internal electrolyte and osmotic homeostasis in aquatic ectotherms (Christensen 1975;Amoudi et al 1996;Metz et al 2003;Sardella et al 2004Sardella et al , 2008a. It is due to active ion-transporting mechanisms that are regulated by many proteins, while the cellular proteins of stenothermal species are only marginally stable at a limited range of temperature (Hochachka and Somero 2002;Metz et al 2003;Crockett and Londraville 2006;Sardella et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation